KEWARISAN ISLAM DALAM PERSPEKTIF HISTORIS - Khaiyyul Millati Waddin, Aufal Hadliq (Mabahits : Jurnal Hukum Keluarga Islam, 2024)
This research aims to explore the evolution of the Islamic inheritance system from pre-Islamic times to the modern era, focusing on the significant changes that occurred after the advent of Islam and contemporary legal reforms. The research method used is a literature study, with analysis of historical literature and modern studies related to the application of inheritance law in Muslim countries. The results show that before Islam, the inheritance system was very patriarchal, with women having no inheritance rights. After Islam came, the Qur’an introduced a more equitable system, granting inheritance rights to women, although their share was smaller than that of men. In the modern era, some Muslim countries have made reforms to accommodate gender equality, but the challenge of implementing more equal laws still exists in some countries. This study recommends the need for comparative studies among Muslim countries to analyse the effectiveness of inheritance law reforms, as well as further research on the socio-economic impact of these reforms on women’s welfare. Empirical research is also needed to understand the influence of local socio-cultural factors in the application of Islamic inheritance law.